Translational control and the unfolded protein response - Wek, Ronald C; Cavener, Douglas R (Antioxidants & redox signaling, 2007)
Cellular stresses that disrupt the processing of proteins slated for the secretory pathway induce the unfolded protein response (UPR), a regulatory network involving both translational and transcriptional control mechanisms that is designed to expand the secretory pathway and alleviate cellular injury. PERK (PEK/EIF2AK3) mediates the translational control arm of the UPR by enhancing phosphorylation of eIF2. Phosphorylation of eIF2 reduces global protein synthesis, preventing further overload of the secretory pathway and allowing the cell to direct a new pattern of mRNA synthesis that enhances the processing capacity of the endoplasmic reticulum (ER). PERK also directs preferential translation of stress-related transcripts, including that encoding ATF4, a transcriptional activator that contributes to the UPR. Reduced global translation also leads to reduced levels of key regulatory proteins that are subject to rapid turnover, facilitating activation of transcription factors such as NF-B during cellular stress. This review highlights the mechanisms by which PERK monitors and is activated by accumulated misfolded protein in the ER, the processes by which PERK regulates both general and gene-specific translation that is central for the UPR, and the role of PERK in the process of cellular adaptation to ER stress and its impact in disease.